2018
DOI: 10.2298/tsci180308167b
|View full text |Cite
|
Sign up to set email alerts
|

Improving thermal stability and reduction of energy consumption by implementing Trombe wall construction in the process of building design: The Serbia region

Abstract: Original scientific paper https://doi.org/10.2298/TSCI180308167B This paper analyzes the impact of Trombe wall construction on heating and cooling demands of building with form (rectangular single-store building of about one hundred square meters area) which is common for individual residential buildings in the Republic of Serbia. Trombe wall, as a representative of a passive solar design, was installed on the south wall of the building. Model of the building was made in the Google SketchUp software, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This segment is very important in the context of energy efficiency and much work has been done in this area. Some of the measures for reduction of energy consumption include implementing Trombe wall [15], double skin [7] or improvement of building envelope characteristics [12] and can result in reduction of CO2 emission [13]. ▪ Esthetical.…”
Section: Architectural Structuresmentioning
confidence: 99%
“…This segment is very important in the context of energy efficiency and much work has been done in this area. Some of the measures for reduction of energy consumption include implementing Trombe wall [15], double skin [7] or improvement of building envelope characteristics [12] and can result in reduction of CO2 emission [13]. ▪ Esthetical.…”
Section: Architectural Structuresmentioning
confidence: 99%
“…The cooling effect of the wind is significant only in particular circumstances, e.g. when the weather is very sunny or when the wind is carrying colder air (Bogdanoviċ et al, 2018). If the outside temperature is lower than the internal temperature, the wind can cause convections in or between the insulations, cooling down the inner wall surface.…”
Section: External Iaq Factorsmentioning
confidence: 99%
“…Bogdanovic et al numerically simulated the energy need of a "passive house" with Trombe wall. It was shown that the Trombe wall is an effective means of utilizing solar energy and can provide an effective means for the design of passive houses in the Belgrade area [20]. Martin Thalfeldt explored the facade structure of "net zero energy buildings" in cold regions.…”
Section: Introductionmentioning
confidence: 99%